2017
DOI: 10.4103/0259-1162.181431
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexmedetomidine as an adjuvant to 0.75% ropivacaine in interscalene brachial plexus block using nerve stimulator: A prospective, randomized double-blind study

Abstract: Background:Ropivacaine, a newer local anesthetic (LA), has been increasingly used nowadays in different concentrations for peripheral nerve blocks. It has lesser cardiac toxicity and higher safety margin when compared to bupivacaine. Dexmedetomidine, a novel α2 agonist, is widely used as adjuvant to LA in peripheral nerve blocks to decrease the time of onset and increase the duration of the block. In this study, we evaluated the effect of dexmedetomidine as an adjuvant with 0.75% ropivacaine for interscalene b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
8
11
0
1
Order By: Relevance
“…[ 2 ] Regarding, MBP changes;results showed statistically significance in our study for dexmedetomidine This came in agreement with Rashmi and Komala. [ 14 ] Regarding onset of sensory and motor anesthesia, results showed statistically significance in our study for dexmedetomidine as adjuvant which has earlier onset of anesthesia than fentanyl group and control group while fentanyl has earlier onset than control group which came in agreement with Bharti et al . and Rajkhowa et al .…”
Section: Discussionsupporting
confidence: 90%
“…[ 2 ] Regarding, MBP changes;results showed statistically significance in our study for dexmedetomidine This came in agreement with Rashmi and Komala. [ 14 ] Regarding onset of sensory and motor anesthesia, results showed statistically significance in our study for dexmedetomidine as adjuvant which has earlier onset of anesthesia than fentanyl group and control group while fentanyl has earlier onset than control group which came in agreement with Bharti et al . and Rajkhowa et al .…”
Section: Discussionsupporting
confidence: 90%
“…3 ). And adding dexmedetomidine to ropivacaine obviously decreased the time to sensory block onset both in groups with dosage greater [ 12 , 14 , 16 21 , 23 ] (MD, −2.97 minutes, 95% CI −4.94 to −1.01 minutes, I 2 = 86%; P = .003) and less [ 13 , 15 , 22 ] (MD, −6.96 minutes, 95% CI −11.85 to −2.06 minutes, I 2 = 86%; P = .005) than 50 μg (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most authors have similarly reported (using 100 µg dexmedetomidine) side effects of dexmedetomidine such as hypertension, hypotension, bradycardia or hyperglycemia [22,23]. Rashmi et al used 50 µg dexmedetomidine instead of 100 µg and found that though there was a reduction in heart rate and blood pressure, the drop was not significant enough to warrant specific treatment [24]. Swami et al also found in their study that a group treated with 1 µg/kg dexmedetomidine added to LA had lower heart rate (HR) and blood pressure (BP) as compared to a group treated with 1 µg/kg clonidine added to LA [25].…”
Section: Discussionmentioning
confidence: 99%